Sex-specific associations of testosterone with prefrontal-hippocampal development and executive function. (February 2017) - Nguyen, Tuong-Vi; Lew, Jimin; Albaugh, Matthew D.; Botteron, Kelly N.; Hudziak, James J.; Fonov, Vladimir S.; Collins, D. Louis; Ducharme, Simon; McCracken, James T.
Highlights: Testosterone is associated with prefrontal-hippocampal structural covariance in boys. Testosterone-related covariance is associated with lower executive function in boys. No effect of testosterone on prefrontal-hippocampal covariance was seen in girls. No effect of testosterone-related covariance on executive function was seen in girls. Abstract: Testosterone is thought to play a crucial role in mediating sexual differentiation of brain structures. Examinations of the cognitive effects of testosterone have also shown beneficial and potentially sex-specific effects on executive function and mnemonic processes. Yet these findings remain limited by an incomplete understanding of the critical timing and brain regions most affected by testosterone, the lack of documented links between testosterone-related structural brain changes and cognition, and the difficulty in distinguishing the effects of testosterone from those of related sex steroids such as of estradiol and dehydroepiandrosterone (DHEA). Here we examined associations between testosterone, cortico-hippocampal structural covariance, executive function (Behavior Rating Inventory of Executive Function) and verbal memory (California Verbal Learning Test-Children's Version), in a longitudinal sample of typically developing children and adolescents 6–22 yo, controlling for the effects of estradiol, DHEA, pubertal stage, collection time, age, handedness, and total brain volume. We found prefrontal-hippocampal covariance to vary as a function of testosterone levels, but only in boys. Boys also showed a specific association between positive prefrontal-hippocampal covariance (as seen at higher testosterone levels) and lower performance on specific components of executive function (monitoring the action process and flexibly shifting between actions). We also found the association between testosterone and a specific aspect of executive function (monitoring) to be significantly mediated by prefrontal-hippocampal structural covariance. There were no significant associations between testosterone-related cortico-hippocampal covariance and verbal memory. Taken together, these findings highlight the developmental importance of testosterone in supporting sexual differentiation of the brain and sex-specific executive function.